2013
DOI: 10.1093/infdis/jit100
|View full text |Cite
|
Sign up to set email alerts
|

Unique Vaginal Microbiota That Includes an Unknown Mycoplasma-Like Organism Is Associated With Trichomonas vaginalis Infection

Abstract: T. vaginalis may alter the vaginal microbiota in a manner that is favorable to its survival and/or transmissibility. An unknown Mycoplasma species plays a role in some of these transformations. In other cases, these changes may result in a heightened host inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 45 publications
3
64
0
4
Order By: Relevance
“…We also detected sequence variants corresponding to Trichomonas-associated Candidatus Mycoplasma girerdii (25)(26)(27), and Trichomonas was indeed present in all samples with frequency >10 −3.5 . No STI organism was significantly associated with PTB (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…We also detected sequence variants corresponding to Trichomonas-associated Candidatus Mycoplasma girerdii (25)(26)(27), and Trichomonas was indeed present in all samples with frequency >10 −3.5 . No STI organism was significantly associated with PTB (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…JX508800) is 99% identical to our infant-derived OTU (Fig. S4); this clone was isolated from a vaginal swab from a Trichomonas vaginalis -infected patient (37). Finally, we amplified and cloned near-full-length 16S rRNA gene sequences from baby 3’s DOL 18 saliva (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 73%
“…S4 in the supplemental material). Intriguingly, a recent study found high abundances of this uncultivated Mycoplasma in the vaginal microbiota of Trichomonas vaginalis -infected women (detected in 19/30  T. vaginalis -infected and 1/29 uninfected individuals) (37), again raising the possibility that this organism too was transferred from mother to infant at delivery. Further investigation into the diversity, distribution, and clinical significance of this novel, uncultivated Mycoplasma in human hosts is warranted, particularly in pregnant women and premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…and Gardnerella spp. [111], suggesting that T. vaginalis directly influences or is influenced by the microbial environment and confirming the potential importance of interactions between T. vaginalis and vaginal microbiota.…”
Section: Management and Treatmentmentioning
confidence: 83%